2015
DOI: 10.1002/adsc.201400824
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Preparation of 3‐Arylcycloalkylamines by Rhodium‐Catalyzed 1,4‐Addition and Subsequent Stereodivergent Reduction

Abstract: N‐Sulfonylimines of cycloalk‐2‐enones are well‐suited for the enantioselective rhodium(I)/binap‐catalyzed 1,4‐additions of arylzinc halides. The cyclic enamides, obtained after quenching, are sensitive towards chromatography, but can undergo diastereoselective reductions to furnish cis‐ or trans‐3‐arylcycloalkylamines with five‐ to seven‐membered rings. The 1,4‐addition is not influenced by a methyl group at C‐5 of six‐membered rings, providing further configurational options. 3‐Arylcycloalkylamines are subuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…142 Some 379a-j are key intermediates in the synthesis of biologically active compounds. 339,340 The presence of the chlorosilane is vital for obtaining the 1,4-addition adducts in high yields (Scheme 188). 142 The stereochemical logic and outcome of the 1,4-addition reaction catalyzed by Rh/(R)-binap can be reorganized by the a-si-face attack of the enal, which avoids steric repulsion between the phenyl moiety on the phosphorus atom of (R)-binap and the carbonyl group of the enal (Fig.…”
Section: Organozincsmentioning
confidence: 99%
“…142 Some 379a-j are key intermediates in the synthesis of biologically active compounds. 339,340 The presence of the chlorosilane is vital for obtaining the 1,4-addition adducts in high yields (Scheme 188). 142 The stereochemical logic and outcome of the 1,4-addition reaction catalyzed by Rh/(R)-binap can be reorganized by the a-si-face attack of the enal, which avoids steric repulsion between the phenyl moiety on the phosphorus atom of (R)-binap and the carbonyl group of the enal (Fig.…”
Section: Organozincsmentioning
confidence: 99%
“…Tomioka et al reported on the 1,4-addition of dialkylzinc to N-sulfonyl imines derived from cinnamaldehyde and achieved up to 91% ee using a Cu/amidophosphane catalyst if the sulfonyl group carried a bulky aryl substituent. 13 Both 3-aryl-as well as 3-alkyl-substituted cycloalkyl amines are commonly found in pharmaceutically active molecules. Up to 80% ee was achieved using a Cu/binol-phosphoramidite catalyst in the case of N-2-pyridylsulfonyl imines, while no conversion occurred with the respective tosyl derivatives.…”
mentioning
confidence: 99%
“…In the absence of the chiral ligand and even without the copper salt, some background reactivity was observed (entries 8 and 9), and screening of several copper(I) and copper(II) sources led to only slight variations in the yields (entries [10][11][12][13][14]. In the end, CuTC (TC = thiophene-2carboxylate) was chosen due to its chemical stability, and the reaction was monitored using continuous IR detection which revealed an induction period of about 0.5 min after addition of ZnEt 2 to the catalyst-substrate mixture (see ESI †).…”
mentioning
confidence: 99%
See 2 more Smart Citations